EVALUASI INTERAKSI OBAT DALAM SATU LEMBAR RESEP DAN KELENGAPAN DAFTAR TILIK ALERGI OBAT PASIEN RAWAT JALAN RUMAH SAKIT X JAKARTA - Chusun, Chusun; Poppy, indrianti; Harun, Alam Nur (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Clinical pharmacy services are direct services provided by pharmacists to patients in order to improve therapeutic outcomes and minimize the risk of side effects because the aim of using drugs is for patient safety. One of the clinical pharmacy services provided is assessment and prescription services which must be in accordance with clinical requirements, including the absence of drug interactions and patient allergy records. Based on clinical significance, the severity of drug interactions is classified into three, namely Major, Moderate and Minor. This research uses descriptive methods with retrospective data. The population in this study was all outpatient prescription sheets served from 1 October to 31 December 2023. Sampling used simple random sampling and determining the sample size using the Slovin formula so that the sample used was 460 prescription sheets. Identify drug interactions in one prescription sheet using the Drug Interaction Checker application (Drugbank.com). Results The research showed that of the 460 prescriptions examined, 301 prescriptions had the potential for drug interactions (65.4%), and 320 prescriptions (69.6%) completed the drug allergy checklist. The highest level of drug interactions was at moderate severity, namely 102 prescriptions (33.9%), and minor at 88 prescriptions (29.2%), and the lowest at major severity was 15 prescriptions (5%). If we look at the drug items in one prescription sheet, it can be concluded that there are 506 incidents with the highest level of severity at moderate level, namely 254 incidents (50.2%), which should be avoided in combination or only used in special circumstances and with close monitoring of health workers. While there were 219 minor interactions (43.3%); and major 33 events (6.5%), where this drug combination should not have been given.